Panel Data Analysis With Mediating Variables In The Production Performance Model In Malang City Industry - Meilina Retno Hapsari; Mitha Endah Aprilia; Maulana Abdul Rahman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The development of the industrial sector is able to provide a strategic role in the economy. One of the efforts made to improve industrial performance is to find out the factors that influence production performance in industry. This research has a purpose to determine the effect of number of workers and production quantity on production performance as seen from production value in Malang City Industry, where production quantity is a mediating variable. This research is quantitative research. This data source is secondary data from Malang City Industrial data. The samples in this research were small and medium industries in Malang City for several years. Based on the panel data analysis result with mediating variables, show the number of workers has a significant effect on the amount of production. The number of workers does not have a significant effect on production performance. The amount of production has a significant effect on production performance. The number of workers has a significant effect on production performance through the amount of production. Therefore, it is hoped that industrial leaders need to increase the number of workers so that production increases, and the increased production will increase the performance of industrial production in Malang City.